SAINS BUMI DAN ANTARIKSA PADA ANAK USIA DINI - Selfi Lailiyatul Iftitah; Mardiyana Faridhatul Anawaty (PROGRAM STUDI PENDIDIKAN ISLAM ANAK USIA DINI STAI DINIYAH PEKANBARU, 2023)
The concept of science developed for the context of early childhood is so that children have insight and experience about events in their surroundings. Early childhood has a high curiosity about science. So that the process of early childhood learning about science is to develop a child's curiosity about the surrounding environment. Earth and space science is one of the fields of science for early childhood learning. The learning can be in the form of objects in the surrounding environment or natural events that occur. Therefore, it will be discussed about the concept of earth and space science in early childhood. The research method used is literature study (literature study) with relevant written sources. Earth Science covers objects and events on earth such as air, air, soil, rock, as well as natural disasters. Meanwhile, space science consists of objects in outer space, such as the sun, moon, stars, as well as the events that cause them, for example the existence of day and night, temperature differences and changing seasons. Several indicators developed at an early age related to the science of the Earth and Space area, namely knowledge of the properties of earth materials, use of vocabulary that displays day and night, observations about individual activities that can cause changes that occur in materials, observations about the weather.